Analisis Struktural dan Nilai Pendidikan Karakter dalam Novel “Orang-Orang Biasa” karya Andrea Hirata serta Pemanfaatannya Sebagai Bahan Ajar Berbasis TPACK di SMA - Kurniawati, Epa (Jurnal Artikula, 2025)
This study aims to analyze the intrinsic elements and character education values ​​in the novel "Orang-Orang Biasa" by Andrea Hirata and explore its use as a TPACK-based teaching material. This research method uses a qualitative description method using content analysis techniques, to identify and examine the meaning of the intrinsic elements and character education values ​​in the novel. Based on the results of the analysis, the novel Orang-Orang Biasa by Andrea Hirata contains character education values ​​such as responsibility, care, respect, discipline, patriotism and nationalism. The intrinsic structure of the novel includes the theme of life's struggle, with a plot that raises social conflict. The characters in the novel show an attitude of solidarity and courage in facing various challenges. As a TPACK-based teaching material, technology such as Canva can be used to make it easier for students to understand and analyze the structure and character values ​​in the novel interactively. This study is recommended as a learning material for Indonesian language and literature to improve students' understanding of the intrinsic structure and character education values ​​in literary works, especially the novel Orang-Orang Biasa. Through the TPACK approach, this learning can strengthen literacy skills, technology, and literature teaching in schools, as well as encourage the development of positive character in students.